Sorption of neptunium on clays and clay minerals: a review - Fröhlich, Daniel R. (Clays and clay minerals, 2015)
During recent decades, the search for possible repositories for high-level nuclear waste has yielded large amounts of sorption data for actinides on different minerals. Clays and clay minerals are of special interest as potential host-rock formations and backfill materials, by virtue of their good retardation properties. Neptunium (Np) is one of the actinides which is considered in long-term scenarios due to its long-lived nuclide 237Np (t1/2 = 2.1 × 106 y). Because neptunium sorption is heavily dependent on the experimental conditions, comparison of sorption data from different experiments is challenging. Normalizing reported data with respect to the surface area of the sorbent enables conversion of conventional distribution coefficients (Kd) to normalized (Ka) values, which improves comparability among the results of different experiments. The present review gives a detailed summary of sorption data of Np on clays and clay minerals and examines critically the applicability of the Ka approach.